1995
DOI: 10.1007/bf02048338
|View full text |Cite
|
Sign up to set email alerts
|

Multiple vaginal deliveries increase the risk of permanent incontinence of flatus and urine in normal premenopausal women

Abstract: These results indicate that repeated vaginal deliveries increase the risk of minor anal and urinary incontinence, which were found to be a common problem in premenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
3
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(64 citation statements)
references
References 13 publications
8
51
3
2
Order By: Relevance
“…We have already discussed pudendal neuropathy in relation to urinary incontinence; the neurogenic basis of fecal incontinence is even better established (Snooks et al, , 1985Sultan et al, 1994;Ryhammer et al, 1995;Kafka et al, 1997;Jackson, 1998). Pudendal nerve injury and traumatic anal sphincter disruption subsequent to vaginal delivery are the two primary causes of fecal incontinence (Jackson, 1998).…”
Section: Maintains Fecal Continencementioning
confidence: 97%
See 1 more Smart Citation
“…We have already discussed pudendal neuropathy in relation to urinary incontinence; the neurogenic basis of fecal incontinence is even better established (Snooks et al, , 1985Sultan et al, 1994;Ryhammer et al, 1995;Kafka et al, 1997;Jackson, 1998). Pudendal nerve injury and traumatic anal sphincter disruption subsequent to vaginal delivery are the two primary causes of fecal incontinence (Jackson, 1998).…”
Section: Maintains Fecal Continencementioning
confidence: 97%
“…This suggests a double neuromuscular pathology: direct compression, stretch, and devascularization of the pudendal nerve resulting in levator ani atrophy and loss of urethral and bladder support. Ryhammer et al (1995) reported on the relationship between urinary incontinence symptomatology and the number of repeated vaginal deliveries. The risk for urinary incontinence was additive: 3.3%, 1.0%, and 6.8% after one, two, and three deliveries, respectively.…”
Section: Maintains Urinary Continencementioning
confidence: 98%
“…The first symptoms of urinary incontinence can arise after the first pregnancy and the risk of incontinence increases with multiple deliveries [584]. However, the sensitivity of the rat detrusor muscle to ATP was not modified by multiple pregnancies, while there was increased sensitivity to adrenergic and cholinergic stimulation [273].…”
Section: Changes Occurring During Pregnancy or Hormone Therapiesmentioning
confidence: 99%
“…In 1995, Ryhammer et a1. 19 reported that multiple vaginal deliveries increased the risk of permanent incontinence.…”
Section: Introductionmentioning
confidence: 99%